Clustered macrophages cooperate to eliminate tumors via coordinated intrudopodia - Lawrence J. Dooling; Alişya A. Anlaş; Michael P. Tobin; Nicholas M. Ontko; Tristan Marchena; Maximilian Wang; Jason C. Andrechak; Dennis E. Discher (Proceedings of the National Academy of Sciences, 2025)
Macrophages often pervade solid tumors, and clusters of macrophages sometimes associate with longer survival of patients. However, clustering mechanisms and impacts on key functions such as phagocytosis remain obscure. Here, under conditions that maximize cancer cell phagocytosis within cohesive tumors, we uncover pathways that favor dynamic clusters and find a colocalization of tumor-intrusive pseudopodia which we term “intrudopodia.” Cluster formation over hours on low-adhesion substrates occurs after macrophage induction to a state colloquially referred to as M1 after exposure to interferons and T cell–derived cytokines. Clusters prove fluid on timescales of minutes and also sort from interleukin-4-treated, so-called M2 macrophages that tend to disperse. M1 macrophages upregulate specific cell–cell adhesion receptors but suppress actomyosin contractility, with both pathways contributing to cluster formation. Decreased cortical tension was not only reflected in a low level of nuclear lamin-A that downregulates cytoskeletal targets of serum response factor and tends to soften the nucleus but was also predicted to unleash pseudopodia. Macrophage neighbors in tumor spheroids indeed coextend intrudopodia between cancer cell junctions—at least when phagocytosis conditions are maximized. Intrudopodia from neighbors help detach and individualize cancer cells for rapid engulfment. Juxtaposition of a macrophage cluster with tumor cell nests defines a broad interface that minimizes cancer cell nearest neighbor interactions and maximizes coordination of macrophage intrudopodia. Cooperative phagocytosis thus overcomes solid tumor cohesion—and might explain why the macrophage clustering factor ITGAL associates with patient survival.